2021
DOI: 10.1002/vzj2.20122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evolving salt precipitation on the evaporation and temperature of sandy soil with a fixed groundwater table

Abstract: The effects of salt precipitation on water and heat transport in soil have garnered considerable attention. However, salt precipitation growth on the soil surface and its influence on soil evaporation and temperature under a fixed groundwater table are not well understood. Therefore, the objective of this study was to investigate the impact of the evolution of salt precipitation on evaporation and temperature in sandy soils with a fixed groundwater table depth (20 cm). The laboratory experiment consisted of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…However, upward salt growth was observed in fine sand, although this increase in salt growth did not simply increase the thickness but formed a salt dome (Figures 2 and 3). Salt precipitation by NaCl tends to form salt domes over the matrix surface, resulting in a salt crust that was separated from the sand surface, which has been reported in several studies [23][24][25][26][27]. Figure 6(a) clearly shows that salt domes were formed on the surface of fine sand, and some salt crust was elevated and separated from the sand surface.…”
Section: Salt Precipitation In Homogeneoussupporting
confidence: 59%
See 1 more Smart Citation
“…However, upward salt growth was observed in fine sand, although this increase in salt growth did not simply increase the thickness but formed a salt dome (Figures 2 and 3). Salt precipitation by NaCl tends to form salt domes over the matrix surface, resulting in a salt crust that was separated from the sand surface, which has been reported in several studies [23][24][25][26][27]. Figure 6(a) clearly shows that salt domes were formed on the surface of fine sand, and some salt crust was elevated and separated from the sand surface.…”
Section: Salt Precipitation In Homogeneoussupporting
confidence: 59%
“…e height of the salt domes also increased with time in the fine sand. e upward growth of salt precipitation to form salt domes has been investigated in various media textures [23][24][25][26][27][28], but no studies have reported that it is related to particle size. erefore, this study presents new insights into the relationship between the pattern of salt precipitation and texture of the matrix.…”
Section: Salt Precipitation In Homogeneousmentioning
confidence: 99%
“…Salt accumulation in the topsoil of arid regions causes salt precipitation (Norouzi Rad et al, 2013; Shokri‐Kuehni, Vetter, et al, 2017), which, in porous media, can affect evaporation (Li & Shi, 2021a; Nachshon, Shahraeeni, et al, 2011; Norouzi Rad et al, 2015), soil temperature (Li & Shi, 2021a; Shokri‐Kuehni, Vetter, et al, 2017), wind erosion (Nickling & Ecclestone, 1981; Nield et al, 2016) and rock decay (Benavente et al, 2010; Rodriguez‐Navarro & Doehne, 1999; Ruiz‐Agudo et al, 2007). Salt can be precipitated as efflorescence on the soil surface in ‘crusty’ or ‘patchy’ patterns (Eloukabi et al, 2013) based on the matrix texture, or as subflorescence within soil pores (Rodriguez‐Navarro & Doehne, 1999) based on the salt type.…”
Section: Introductionmentioning
confidence: 99%
“…Salt crusts are a typical soil structure that forms as a consequence of soil enrichment and bonding due to salt accumulation [12]. Soil salt crusts are a type of soil surface crust that usually exhibits high concentrations of salt, and they are observed in arid lands with shallow groundwater tables [13][14][15]. Salt crusts have also been reported to form strong surfaces that resist deflation and have a high-threshold friction velocity, to reduce dust Land 2022, 11, 999 2 of 15 emissions, and to stabilize the underlying surface, which is an important factor in resistance against wind erosion for scarce vegetation [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%